Global desert expansion during the 21st century: Patterns, predictors and signals. (7th October 2022) - Wu, Shuyao; Liu, Laibao; Li, Delong; Zhang, Wentao; Liu, Kaidu; Shen, Jiashu; Zhang, Linbo
Abstract: Desert expansion can cause tremendous damage to human wellbeing. However, the process of shifting from the non‐desert state to the desert state, a representation of a system regime shift, remains unclear on a global scale. Clarifying the underpinning patterns, predictors and signals of this process is of great value in advancing our understanding of both ecosystem resilience and sustainable development. Here, we combine the climate classification map and long‐term observational land cover data to assess the global desert distribution and its changes from 2000 to 2019. The identified desert areas covered approximately 7.53% of the global land in the past two decades. Only approximately 16.03% of these deserts showed expanding trends, especially in countries such as Tunisia, Tajikistan, and Peru. After assessing 26 climatic, ecological, and socioeconomic factors that could potentially influence desert expansion rates, vegetation cover diversity was identified as the strongest predictor in both hot and cold deserts, followed by cattle density in hot deserts and desert size in cold deserts. In addition, we also found that pronouncedly high fluctuations in vegetation productivity could serve as a possible signal for desert conversion. Our results provide not only a long‐term overview of current global desert changing patterns but also possible guidance for constraining desert expansion.